Facing alternative futures: prospects for and paths to food security in Africa - Rosegrant, Mark W.; Cline, Sarah A.; Li, Weibo; Sulser, Timothy B.; Valmonte-Santos, Rowena (International Food Policy Research Institute, 2005)
Food security in Africa has substantially worsened since 1970. Although the proportion of malnourished individuals in Sub-Saharan Africa has remained in the range of 33–35 percent since around 1970, the absolute number of malnourished people in Africa has increased substantially with population growth, from around 88 million in 1970 to an estimate of over 200 million in 1999–2001. Yet this discouraging trend need not be a blueprint for the future. New research from IFPRI shows that the policy and investment choices of African policymakers and the international development community can make an enormous difference for Africa’s future agricultural production and food security. By modeling the results of a number of different policy scenarios in Africa through the year 2025, we show that the number of malnourished children, one important indicator of food security, could rise as high as 41.9 million or fall as low as 9.4 million. These scenarios, therefore, shed light on the effectiveness of various policies and investments in assuring a food-secure future for Africa.